Transcending Gender: Toward a New Awareness of the Fluid Self in Writing - Jack Ramey (Journal of the Assembly for Expanded Perspectives on Learning, 1996)
The constructs of the male and female in the gendered self are not binary opposites but interlocking halves of an inseparable whole.